Legal Certainty of The Status of 3 (Three) Kilograms of Gas As A Strategic Goods Free From VAT (Value Added Tax) - Mulyadi Mulyadi (Ilmu Hukum Prima (IHP), 2025)
This study aims to examine in depth the normative conflict arising from the enactment of Minister of Finance Regulation (PMK) Number 62/PMK.03/2022 concerning Value Added Tax  (VAT)  on  the  delivery  of  certain  Liquefied  Petroleum  Gas  (LPG),  specifically subsidized  3  kg  LPG  cylinders,  against  regulations  that  have  a  higher  position  in  the hierarchy of laws and regulations. The PMK stipulates that the unsubsidized portion of the price of 3 kg LPG is subject to VAT and must be collected by agents down to the base level, which is then passed on to the end consumer. This policy has caused controversy because it conflicts with several higher regulations, such as Law Number 42 of 2009 concerning VAT, Law  Number  7  of  2021  concerning  Harmonization  of  Tax  Regulations  (UU  HPP),  and Presidential Regulation Number 71 of 2015 concerning Determination and Storage of Basic Necessities and Important Goods.Through a normative legal approach, this study sought to obtain  the  necessary  data  related  to  the  problem.  The  data  used  were  secondary  data, consisting of primary legal materials, secondary legal materials, and tardier legal materials. In addition, premium data was also used as secondary data. Data analysis was conducted using a normative legal analysis method. This study found that PMK 62/2022 does not align with the principle of the hierarchy of legal norms as proposed by Hans Kelsen, where lower norms  must  not  contradict  higher  norms.This  study  concludes  that  PMK  62/2022 constitutes a form of vertical norm conflict that not only contradicts higher positive law but also  contradicts  the  principles  of  social  justice  as  stipulated  in  Pancasila  and  the  1945 Constitution.  Therefore,  policy  revision  or  revocation  of  this  regulation  is  necessary  to ensure legal harmony, legal certainty, and protection for vulnerable communities.